2020
DOI: 10.1177/0030222820965311
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Indian Medical and Nursing Students Towards Euthanasia: A Cross-Sectional Survey

Abstract: This cross-sectional survey was carried out among medical internees (n = 92) and nursing students (n = 228) to investigate their attitudes towards euthanasia. The data was collected by administering a Euthanasia Attitude questionnaire. The findings revealed that a majority (61%) of the participants were in support of euthanasia. Yet ethical dilemmas prevail among students about active and passive euthanasia and legalization of euthanasia. Further, age, gender, religion, education and exposure to patients who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Their general perception of whether or not they felt prepared and able to engage in this practice is consistent with previous studies (Crusat-Abelló and Fernández-Ortega, 2021), i.e. while recognising that euthanasia is a common, necessary good, they feel that more training is needed in this regard (Poreddi et al, 2020) and that they do not believe they are educated to manage such a decisive situation in someone's life. This situation can lead to what other studies refer to as moral distress among nursing students as a consequence of the great difficulty of making ethically and morally important decisions without adequate preparation and decision-making skills, especially in scenarios involving requests for hastened death (Range and Rotherham, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Their general perception of whether or not they felt prepared and able to engage in this practice is consistent with previous studies (Crusat-Abelló and Fernández-Ortega, 2021), i.e. while recognising that euthanasia is a common, necessary good, they feel that more training is needed in this regard (Poreddi et al, 2020) and that they do not believe they are educated to manage such a decisive situation in someone's life. This situation can lead to what other studies refer to as moral distress among nursing students as a consequence of the great difficulty of making ethically and morally important decisions without adequate preparation and decision-making skills, especially in scenarios involving requests for hastened death (Range and Rotherham, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Some studies showed that students opposed the legalization of euthanasia ( 16 , 18 , 29 ). In other studies, students supported the legalization of euthanasia ( 33 , 43 ). In addition, it has been observed that most students don't want to take part in the application of euthanasia if it were legal ( 16 , 18 , 33 ).…”
Section: Discussionmentioning
confidence: 84%
“…In other studies, students supported the legalization of euthanasia ( 33 , 43 ). In addition, it has been observed that most students don't want to take part in the application of euthanasia if it were legal ( 16 , 18 , 33 ). The results are similar to our study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…V. Poreddi, N. Reddy SS, and D. R. Pashapu, 2022 [14] The results of the research showed that the majority have a positive attitude towards the implementation of euthanasia. There were significant differences between students' attitudes and socio-demographic variables regarding euthanasia.…”
Section: Author and Yearmentioning
confidence: 96%